Prognostic significance of cerebro-placental ratio in predicting perinatal - Negi, Priyanka; Choudhary, Anjali; Kaushik, Srishti; Nimonkar, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cerebro-placental ratio (CPR), measured by Ultrasound Doppler velocimetry in pregnancy, has gained much attention in recent years as an important tool in predicting perinatal outcomes. The study aimed to calculate the cerebro-placental ratio and correlateit with perinatal outcome in terms of intrapartum fetal heart variation, meconium staining of liquor, mode of delivery, Apgar score at birth, and NICU admissions. Methods: It was hospital-based prospective cross-sectional study on 119 pregnant women with high-risk pregnancies. All women had doppler velocimetry ultrasound, and cerebro-placental ration was calculated. Perinatal outcome was noted in terms of FHR variability in labor, Meconium staining of liquor, Apgar score and need for NICU admission. Results: Out of the total of 119 women, 88 women had CPR >1.08 and 31 women had CPR of <1.08. Meconium staining of liquor, low Apgar score, and NICU admission was mound in significantly more babies with low CPR. Conclusions: CPR has a good prognostic value in predicting many adverse perinatal outcomes.